HUQUQSHUNOSLIK FANLARINI O‘QITISHDA NOSTANDART TESTLARDAN FOYDALANISH - Kudaybergenova, T. (SCIENCE and SOCIETY, 2018)
The article deals with the methods of non-standard tests in the subject «Law sciences». The author of the article also studies different types of tests, non-standart tests, their advantages and importance.